Relationship between Fatigue and Physical, Psychological and Situational Factors in Hemodialysis Patients - Zahra Royani; Ghanbar Roohi; Zahra Sabzi; Hamideh Mancheri; Einollah Mollaei (Golestan University of Medical Sciences, 2017)
Background: Fatigue is among the most common complications for hemodialysis patients. The theory of unpleasant symptoms is associated with fatigue in hemodialysis patients. According to this theory, fatigue has three physical, mental and situational factors. Considering this theory,   we aimed to determine some factors related to fatigue in hemodialysis patients. Methods: In this descriptive-analytical study, of 165 hemodialysis patients admitted to Panje Azar Medical and Educational Center in Gorgan, Iran, 58 eligible ones were randomly selected. Data was  collected using demographic information questionnaire, Fatigue Severity Scale, Beck Anxiety Inventory and Beck Depression Inventory. Data analysis was conducted in SPSS 17, using Mann-Whitney, Kruskal-Wallis and Spearman's rank correlation coefficient tests. Results: The mean fatigue in all patients was 4.76 ± 1.66 out of 7. Fifty-two patients (89.7%) suffered from some degree (mild to severe) of anxiety and 43 patients (74.1%) suffered from some degrees (mild to severe) of depression. Fatigue only had a direct relationship with psychological factor [anxiety (P = 0.006, r = 0.353, and depression (P <0.001, r = 0.525)]. Conclusion: Considering the high prevalence of fatigue among hemodialysis patients and associated factors, care providers are advised to identify high-risk individuals through conducting periodic psychiatric examinations and to promote their knowledge on available strategies to reduce adverse effects in these patients.